2001
DOI: 10.1093/humrep/16.11.2418
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of adenomyosis at hysterectomy

Abstract: Our study stresses the need for precise diagnostic criteria for adenomyosis, and furthermore indicates that endometrial hyperplasia and adenomyosis may have a common aetiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
2
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(163 citation statements)
references
References 17 publications
8
139
2
14
Order By: Relevance
“…12 This wide range reflects differences in patient population, histopathological criteria used to diagnose adenomyosis and the diligence with which pathology specimens are examined. [13][14][15] The histological prevalence of adenomyosis in our study falls within the reported range; however the actual prevalence may have been over or under estimated depending on how thoroughly the pathologists examined the hysterectomy specimens.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…12 This wide range reflects differences in patient population, histopathological criteria used to diagnose adenomyosis and the diligence with which pathology specimens are examined. [13][14][15] The histological prevalence of adenomyosis in our study falls within the reported range; however the actual prevalence may have been over or under estimated depending on how thoroughly the pathologists examined the hysterectomy specimens.…”
Section: Discussionsupporting
confidence: 62%
“…2 Uterine enlargement, dysmenorrhoea and menorrhagia are regarded as the cardinal clinical symptoms of adenomyosis. 3,4 It is relatively frequent in multiparous women, in their fourth and fifth decade of life. 5 Risk factors for adenomyosis are age, multiparity, surgical disruption of the endometrial-myometrial border, elevated levels of both FSH and prolactin, smoking habits and history of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of adenomyosis has been a challenge, with hysterectomy being the treatment of choice for severe and symptomatic adenomyosis (2). Hitherto, the molecular mechanisms underlying adenomyosis-associated dysmenorrhea are poorly understood.…”
Section: Anxa2 Knockdown Compromises Growth Metastasis and Proangiomentioning
confidence: 99%
“…It preferentially inflicts multiparous women in their reproductive or perimenopausal years, and its prevalence worldwide has been reported to range from 8.8 to 61.5% in women at the time of hysterectomy (1,2). Approximately two-thirds of adenomyosis patients suffer from dysmenorrhea (15-30%), menorrhagia (40 -50%), metrorrhagia (10 -12%), or even early pregnancy stage miscarriages, thereby greatly compromising their physical, mental, and social well being.…”
mentioning
confidence: 99%
“…In hysterectomy specimens the incidence of adenomyosis reported in the literature varies, ranging from a high of 61.5% to a low of 8.8% (2,5,(11)(12)(13)(14)(15). Hyperestrogenemia, a cause of endometrial hyperplasia and fibroid growth, has been associated with adenomyosis, (5,11) as has prior pregnancy (2,3,13,15,16). Adenomyosis has also been related to the presence of endometriosis (2,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%